TEACHING SPEAKING THROUGH RETELLING STORIES OF CARTOON MOVIES AT JUNIOR HIGH SCHOOL - Rasnel Fahmi Irsyad; Don Narius (Universitas Negeri Padang, 2013)
AbstractThis paper discusses a learning medium, especially for English language teaching to Junior High School students through retelling stories of cartoon movie. By using this media, it can be one of the exciting activities for bringing students interested in learning English with confident . In this activity, students are able to convey his ideas and all students obtain the same opportunities to speak at every meeting. Its activities are oral activities that relax, happy and fun. This Instructional media is expected to be useful for English teachers, so that they will enrich the teaching of speaking techniques. It is also for the students are expected to be able to improve English language skills, motivation and self-confident, and loving the English language in school and outside of school.Key Words: movie, media, siswa smp